PRE-SERVICE ENGLISH TEACHERS' PERCEPTION OF THE USE OF DIGITAL TECHNOLOGY TO CREATE ENGLISH TESTS IN LANGUAGE ASSESSMENT - Jabu, Baso; Asriati, Asriati (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The main objective of this research is to obtain an overview of pre-service English teachers' perceptions regarding the use of digital technology in making English language tests in the language assessment process. This research uses a mixed-method research model that combines qualitative research models and quantitative models to obtain more comprehensive and in-depth data regarding pre-service English teachers' perceptions on the use of digital technology in creating English tests. The research data source will be selected purposively, namely, pre-service teachers who have completed the Language Assessment course in the English Language Education study program, Faculty of Language and Literature, Universitas Negeri Makassar. In the data collection process, researchers used interviews, questionnaires, and document reviews. Qualitative data will be analyzed based on the stages of data reduction, data presentation, and drawing conclusions or verification. Meanwhile, to analyze quantitative data, researchers will use descriptive statistical analysis. The result of this study reveals that the pre-service English teachers portrayed a positive attitude toward the use of digital technology to create English tests in language assessment